Pendampingan Dalam Meningkatkan Kualitas Baca Tulis Al Qur’an Di TPQ Nurul Hidayah Pagesangan Surabaya - Reny Masyitoh; Moch. Nurcholis Majid (PT. Penerbit Riset Sadwa, 2025)
The main issues encountered at TPQ Nurul Hidayah Pagesangan Surabaya include the need to strengthen students’ Qur’anic reading abilities in accordance with tajwid rules and makharijul huruf, uneven proficiency in writing hijaiyyah letters, and limited accuracy in performing wudhu and prayer practices based on fiqh guidelines. These conditions are influenced by limited learning time, varying student abilities, and an imbalance between teachers and students. This Community Service Program aims to enhance students’ Qur’anic literacy and prayer practices through an integrated and sustainable mentoring model. The method employed is Participatory Action Research (PAR), consisting of problem identification, action planning, implementation, observation and evaluation, and reflection. The mentoring activities applied the Tilawati method, guided hijaiyyah writing exercises, and practical wudhu and prayer training using a learning-by-doing approach. The results indicate improvements in reading fluency and accuracy, consistency in hijaiyyah letter writing, and correct implementation of worship practices. This program emphasizes the importance of integrative and participatory mentoring in supporting sustainable improvement of non-formal Islamic education quality